2022
DOI: 10.3390/ijerph20010681
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverages Intake, Abdominal Obesity, and Inflammation among US Adults without and with Prediabetes—An NHANES Study

Abstract: Excessive sugar-sweetened beverages (SSB) consumption and abdominal obesity have been independently linked to numerous disorders, including diabetes and elevated C-reactive protein (CRP). This study aimed to explore the association between SSB intake, abdominal obesity, and inflammation in normal and prediabetic adults. Sugar intake from SSBs was calculated from 24-h dietary recalls and further classified into non-, medium-, and high-intake. The status of non- and prediabetes was identified based on hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The times and occasions for each food item were also obtained. This approach to calculate the amount of SSB intake was in line with previous NHANES studies [17,18].…”
Section: Assessment Of Sugar-sweetened Beverages Intakesupporting
confidence: 59%
“…The times and occasions for each food item were also obtained. This approach to calculate the amount of SSB intake was in line with previous NHANES studies [17,18].…”
Section: Assessment Of Sugar-sweetened Beverages Intakesupporting
confidence: 59%
“…Accumulating evidence supports the role of inflammation in the abnormal changes in blood glucose (34). Lin et al (35) revealed the relationship between excessive intake of sugary drinks and abdominal obesity with diabetes and the elevation of C-reactive protein (CRP) levels, emphasizing the positive correlation between sugar intake and CRP levels in adults with prediabetes. Moreover, Mi et al (36) found that the Dietary Inflammatory Index (DII) is positively associated with insulin resistance in adults of normal and healthy weight, highlighting the potential value of anti-inflammatory diets in the prevention or management of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Sweetened beverages can increase inflammatory biomarkers through their obesity-induced effects. Also, some studies have shown that the positive association between SSBs and inflammatory biomarkers can occur independently of obesity ( 45 ). Given the inflammatory nature of colorectal cancer, SSBs-induced inflammation may adversely affect the prognosis of patients.…”
Section: Methodsmentioning
confidence: 99%